Strategi Pemasaran Dalam Upaya Meningkatkan Jumlah Kunjungan Pasien Di Klinik Klinik Bidan Elidar Kabupaten Aceh Tenggara - Sri Wahyuni Sambo (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Elidar Midwife Clinic Southeast Aceh Regency provides health services located on Jl. Hero of Simpang Empat Village, Lawe Bulan District, Southeast Aceh Regency. The number of patient visits at this clinic tends to stagnate and decline. The research aims to determine the internal and external marketing environment, strengths, weaknesses, opportunities, and threats (SWOT) as well as marketing strategies and increase the number of patient visits at the Elidar Midwife Clinic, Southeast Aceh Regency. Qualitative research method. purposive sampling was used for research subjects. The results of the research analyze the internal environment which includes the strength of service facilities, human resource capabilities, promotion, and tariff setting as well as weaknesses such as inadequate facilities and infrastructure, insufficient human resources, and organizational and financial management that has not been managed well. While external environmental analysis has opportunities in terms of community needs, clinic development, and collaboration with BPJS, there are also threats including doctors on duty who are often empty, limited income, and the presence of competitors such as community health centers, private doctors' practices, midwives, and nurses. The Elidar Midwife Clinic, Southeast Aceh Regency is in the growth quadrant. The strategy that must be implemented is an active growth policy (Growth Oriented Strategy). The company maximizes its strengths and takes advantage of existing opportunities to compete with competitors. This strategy can be formulated through the S-O strategy (Strength-Opportunity Strategy), namely a professional implementation system, increasing human resource education/training programs, expanding market share, and strengthening cooperation.